1970
DOI: 10.3329/bjpbg.v23i1.9317
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence in Groundnut (<i>Arachis hypogaea</i> L)

Abstract: Comprising 34 groundnut genotypes an experiment was conducted in a randomized block design with three replication at the Research farm of Regional Agricultural Research Station, BARI, Hathazari, Chittagong during Rabi season (December 2009 to April 2010) for estimation of the multivariate analysis of divergence. The genotypes were grouped into five clusters. Cluster III contained the highest number of genotypes (12) and the cluster II contained the lowest (2). The inter-cluster distances in all cases were larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…The values of PCV were greater than GCV (values for each of the traits considered in our present experiment), signifying the effect of environment on these characters. The outcome of the present study is in accordance with the reports of Zaman et al (2010), Vishnuvardhan et al (2013), and Rao (2016). Low GCV and PCV values were documented for the traits namely, days-to-first flowering, days-to-maturity, as well as days-to-50% flowering, which indicate that there is hardly any opportunity for genetic enhancement of these characters via selection.…”
Section: Resultssupporting
confidence: 92%
“…The values of PCV were greater than GCV (values for each of the traits considered in our present experiment), signifying the effect of environment on these characters. The outcome of the present study is in accordance with the reports of Zaman et al (2010), Vishnuvardhan et al (2013), and Rao (2016). Low GCV and PCV values were documented for the traits namely, days-to-first flowering, days-to-maturity, as well as days-to-50% flowering, which indicate that there is hardly any opportunity for genetic enhancement of these characters via selection.…”
Section: Resultssupporting
confidence: 92%
“…Sudan is one of most an important countries producer groundnut in the world (Zaman et al, 2010). It is a major oilseed and cash crop, used for food, forage and the enhancement of soil fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on groundnut have been carried out, but has a few attentions and there is limited information regarding its genetics, breeding and production, especially genetic improvement under rain-fed conditions, due to groundnut has a narrow genetic base due to its monophyletic origin, self-pollination and lack of gene flow (Meta and Monpara, 2010). Moreover, to improve and sustain the yield of groundnut under rain-fed condition, plant breeders should have a better understanding of the genetic variability of yield and its components and development of high yielding cultivars with drought tolerant at different stages of crop growth (Reddy et al, 2003;Zaman et al, 2010). Therefore, the objectives of this study were to estimate the genotypic and phenotypic variability, broad sense heritability, morphological and yield associated traits of groundnut genotypes under rain-fed conditions in the semi-arid region of Sudan.…”
Section: Introductionmentioning
confidence: 99%
“…This grouping indicated considerable diversity among the RILs. The inter-cluster distance (Table 2) was larger than the intracluster distance which indicated that greater diversity is present among the genotypes of distant group (Zaman et al, 2010) [12] . The inter-cluster distance analysis shows that the maximum divergence was observed between cluster III and cluster VII (94.866).…”
Section: Methodsmentioning
confidence: 99%